Impact of contract farming on income: Linking small farmers, packers, and supermarket in China - Miyata, Sachiko; Minot, Nicholas; Hu, Dinghuan (International Food Policy Research Institute, 2007)
Contract farming is seen by proponents as a way to raise small-farm income by delivering technology and market information to small farmers, incorporating them into remunerative new markets. Critics, however, see it as a strategy for agribusiness firms to pass production risk to farmers, taking advantage of an unequal bargaining relationship. There is also concern that contract farming will worsen rural income inequality by favoring larger farmers. This study examines these issues in Shandong Province, China, using survey data collected from 162 apple and green onion farmers and interviews with four contracting firms in 2005. Using a probit model to estimate participation in a contract-farming scheme, we find little evidence that contracting firms prefer to work with larger farmers, though all farms in the area are quite small. Furthermore, using a Heckman selection-correction model to control for possible selection bias, we find that contract farmers earn significantly more than independent farmers after controlling for household labor availability, education, farm size, and other characteristics. Finally, we find that the way contracting contributes to farm income varies between commodities: contract apple growers benefit from higher yields (presumably due to technical assistance), while contract green onion growers receive higher prices (presumably due to better quality). These results suggest that contract farming can help small farmers raise their incomes and gain access to the growing urban and export markets. Questions remain regarding the number of farmers that are, or could be, brought into similar contract arrangements.